Comparison of posterior lumbar interbody fusion and transforaminal lumbar interbody fusion in degenerative spondylosis and disc disease in a tertiary care hospital in Pimpri - Kumar, Harsh Sanjay; Swamy, Ajit (International Journal of Research in Orthopaedics, 2020)
Background: Spinal fusion in the form of transforaminal lumbar interbody fusion (TLIF) and posterior lumbar interbody fusion (PLIF) are the two common surgical modalities for degenerative spondylosis and disc disease. The objective of the study to compare blood loss, surgical timing, post-operative medical and surgical complications in patients treated by either modality. Methods: This was to compare prospective study of 30 patients equally divided between two modalities operated for TLIF or PLIF after conservative treatment failure. Results: There is a statistically significant difference between the blood loss, surgical time and improvement in ODI score in two groups while percentage of post-surgical complications are higher in PLIF group compared to TLIF. Conclusions: TLIF is associated with less post-operative surgical complications than TLIF which can be attributed to unilateral exposure of intervertebral disc space and requires lesser operative time and produces less blood loss.